2017
DOI: 10.1242/jcs.200808
|View full text |Cite
|
Sign up to set email alerts
|

Secreted tissue inhibitor of matrix metalloproteinase restricts trans-synaptic signaling to coordinate synaptogenesis

Abstract: Synaptogenesis is coordinated by trans-synaptic signals that traverse the specialized synaptomatrix between presynaptic and postsynaptic cells. Matrix metalloproteinase (Mmp) activity sculpts this environment, balanced by secreted tissue inhibitors of Mmp (Timp). Here, we use the simplified Drosophila melanogaster matrix metalloproteome to test the consequences of eliminating all Timp regulatory control of Mmp activity at the neuromuscular junction (NMJ). Using in situ zymography, we find Timp limits Mmp activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…We further suggest that the synaptic co-localization of Dlp and Mmp1 is mediated through Dlp HS-GAG chains, with Dlp recruiting essential Mmp1 function driving activity-dependent bouton formation. With in situ zymography proteolytic function tests at the synapse (33, 88), we consistently found that reduced Mmp function correlated with Dlp depletion and increased function with Dlp overexpression. However, enzymatic activity appears primarily dependent upon interaction with the Dlp core protein.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We further suggest that the synaptic co-localization of Dlp and Mmp1 is mediated through Dlp HS-GAG chains, with Dlp recruiting essential Mmp1 function driving activity-dependent bouton formation. With in situ zymography proteolytic function tests at the synapse (33, 88), we consistently found that reduced Mmp function correlated with Dlp depletion and increased function with Dlp overexpression. However, enzymatic activity appears primarily dependent upon interaction with the Dlp core protein.…”
Section: Discussionmentioning
confidence: 71%
“…4, 5), we next assayed whether these changes correlate with synaptic proteolytic activity. We used in situ zymography at the NMJ to measure the metalloproteinase-dependent conversion of a dye-quenched fluorogenic gelatin (DQ-gelatin), and quantified fluorescence changes in both the dlp reduction and overexpression conditions used above (33, 88). Although this method cannot differentiate the contributions of different proteases, it provides a live readout of net enzymatic activity through quantifiable fluorescence changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-9 could be released from excitatory inputs to PV expressing neurons. Indeed, MMPs have been noted at synaptic boutons (Shilts and Broadie, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear how octopamine signaling at type I synaptic regions regulates postsynaptic Dlp levels. Broadie and collaborators revealed that ECM metalloproteinases (Mmp1 and Mmp2) and the tissue inhibitor of metalloproteinases (Timp) play critical roles in synapse formation and activity-dependent plasticity in the Drosophila NMJ (Dear et al, 2016(Dear et al, , 2017Shilts and Broadie, 2017). Mmp2 from the presynaptic and postsynaptic compartments has been shown to negatively regulate synaptic Dlp levels at the NMJ, possibly by the proteolytic cleavage of Dlp core proteins (Wang and Page-McCaw, 2014).…”
Section: Discussionmentioning
confidence: 99%